A study on ZrCrNiPtx alloys as negative electrode components for NiMH batteries - Ruiz, Fabricio Carlos (2011)
The effect of the addition of Pt on the electrochemical characteristics of AB2 type ZrCrNi alloys as negative electrode materials for nickelemetal-hydride (NieMH) batteries is studied. Electrochemical characteristics of the alloys like as discharge capacity, activation behavior, high rate dischargeability (HRD) and electrochemical impedance spectroscopy (EIS) were analyzed. The resulting ZrCrNiPtx alloys (x ¼ 0.05 and 0.1 corresponding to 5 wt. % and 10 wt. % respectively) retain the crystalline structure related to hexagonal C14 Laves phases, on both as-melted and annealed samples. Alloy samples containing Pt are found to have a similar activation behavior to the as-melted alloy without Pt. However, this characteristic is improved in annealed samples containing Pt. The discharge capacity of the ZrCrNiPtx alloys is higher than the discharge capacity corresponding to ZrCrNi alloys, except in the case of as-melted ZrCrNiPt0.1 alloy. The addition of Pt also improves significantly the high rate dischargeability, maintaining the capacity values in a wide range of discharge current.